Indatuximab ravtansine plus dexamethasone with lenalidomide or pomalidomide in relapsed or refractory multiple myeloma: a multicentre, phase 1/2a study. Issue 11 (November 2021) - Kelly, Kevin R; Ailawadhi, Sikander; Siegel, David S; Heffner, Leonard T; Somlo, George; Jagannath, Sundar; Zimmerman, Todd M; Munshi, Nikhil C; Madan, Sumit; Chanan-Khan, Asher; Lonial, Sagar; Chandwani, Suraj; et al.
Summary: Background: Indatuximab ravtansine (BT062) is an antibody-drug conjugate that binds to CD138 and synergistically enhances the antitumor activity of lenalidomide in preclinical models of multiple myeloma. This phase 1/2a study was done to determine the safety, activity, and pharmacokinetics of indatuximab ravtansine in combination with immunomodulatory drugs in patients with relapsed or refractory multiple myeloma. Methods: This open-label, phase 1/2a study took place at nine hospital sites in the USA. Eligible patients were aged 18 years or older, had relapsed or refractory multiple myeloma, and ECOG performance status or Zubrod score of 2 or below. Patients who received indatuximab ravtansine with lenalidomide and dexamethasone (indatuximab ravtansine plus lenalidomide) had failure of at least one previous therapy. Patients treated with indatuximab ravtansine with pomalidomide and dexamethasone (indatuximab ravtansine plus pomalidomide) had failure of at least two previous therapies (including lenalidomide and bortezomib) and had progressive disease on or within 60 days of completion of their last treatment. In phase 1, patients received indatuximab ravtansine intravenously on days 1, 8, and 15 of each 28-day cycle in escalating dose levels of 80 mg/m 2, 100 mg/m 2, and 120 mg/m 2, with lenalidomide (25 mg; days 1 to 21 every 28 days orally) and dexamethasone (20–40 mg; days 1, 8, 15, and 22 every 28 days). In phase 2, the recommended phase 2 dose of indatuximab ravtansine was given to an expanded cohort of patients in combination with lenalidomide and dexamethasone. The protocol was amended to allow additional patients to be treated with indatuximab ravtansine plus pomalidomide (4 mg; days 1 to 21 every 28 days orally) and dexamethasone, in a more heavily pretreated patient population than in the indatuximab ravtansine plus lenalidomide group. The phase 1 primary endpoint was to determine the dose-limiting toxicities and the maximum tolerated dose (recommended phase 2 dose) of indatuximab ravtansine, and the phase 2 primary endpoint was to describe the objective response rate (ORR; partial response or better) and clinical benefit response (ORR plus minor response). All patients were analysed for safety and all patients with post-treatment response assessments were analysed for activity. This study is registered with ClinicalTrials.gov, number NCT01638936, and is complete. Findings: 64 (86%) of 74 screened patients were enrolled between July 3, 2012, and June 30, 2015. 47 (73%) patients received indatuximab ravtansine plus lenalidomide (median follow-up 24·2 months [IQR 19·9–45·4]) and 17 (27%) received indatuximab ravtansine plus pomalidomide (24·1 months [17·7–36·7]). The maximum tolerated dose of indatuximab ravtansine plus lenalidomide was 100 mg/m 2, and defined as the recommended phase 2 dose for indatuximab ravtansine plus pomalidomide. An objective response for indatuximab ravtansine plus lenalidomide was observed in 33 (71·7%) of 46 patients and in 12 (70·6%) of 17 patients in the indatuximab ravtansine plus pomalidomide group. The clinical benefit response for indatuximab ravtansine plus lenalidomide was 85% (39 of 46 patients) and for indatuximab ravtansine plus pomalidomide it was 88% (15 of 17 patients). The most common grade 3–4 adverse events in both groups were neutropenia (14 [22%] of 64 patients), anaemia (10 [16%]), and thrombocytopenia (seven [11%]). Treatment-emergent adverse events (TEAEs) that led to discontinuation occurred in 35 (55%) of the 64 patients. Five (8%) patients with a TEAE had a fatal outcome; none was reported as related to indatuximab ravtansine. Interpretation: Indatuximab ravtansine in combination with immunomodulatory drugs shows preliminary antitumor activity, is tolerated, and could be further evaluated in patients with relapsed or refractory multiple myeloma. Funding: Biotest AG.